A guide to data-driven leadership in modern schools - Jones, Leslie, 1970 October 5-; Kennedy, Eugene, 1955- (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
The purpose of this publication is to provide school leaders and other educators with insight into practical uses of data and how to create school cultures conducive to effective data use. Practicing school leaders can benefit from this publication as well as teachers who use data in their classrooms to drive instruction. Another use of this book is for graduate schools that prepare K-12 school leaders.Because of accountability and the importance of data use in schools, data driven decisions and the effective use of data are critical. In A Guide to Data-Driven Leadership in Modern Schools, the use of data as aligned to educational reform is discussed. Accountability and standardized testing are vital elements of reform. The culture must be created in schools to address multi- facets of data use which is presented in Chapter 2 of the publication.The use of data should guide/inform decisions linked to both management and instruction in schools. In Chapter 3, the use of data to inform management is discussed; and the use of data to inform instruction is presented in Chapter 4. Practices of effective management and instructional leadership are obsolete without effective personnel in schools. The use of data in personnel evaluations is explored in Chapter 5.